Priority sectors and industries of the Ukraine's economy: transformations during the war - Husieva, Nataliia; Maliarenko, Kostiantyn; Lymar, Oleksandr (Human Geography Journal, 2024)
Identification of priority sectors and industries of the Ukraine's economy is an important task of state socio-economic policy, especially during a full-scale war. These sectors and industries should be constantly in the focus of the state and Ukrainian society. The livelihoods of citizens and strengthening the state's defense capabilities depend on them. These sectors will become the locomotive for the recovery of the Ukrainian economy in the future. Therefore, the purpose of the article is to identify the priority sectors and industries of the Ukraine's economy before, during and after the end of the full-scale war.Before the full-scale Russian invasion, the priority sectors of the economy were considered to be the sectors aimed at meeting societal needs for high-tech, competitive, environmentally friendly products, high-quality services implementing state policies for developing production and export potential, creating new jobs. Based on this, the priority sectors were agro-industrial complex, housing and communal services, mechanical engineering complex, transport infrastructure, resort and recreational sector and tourism, processing industry, pharmaceutical industry. With the beginning of the full-scale war, Ukraine completely changed its views on the definition and list of priority economic sectors. In the current realities, sectors ensuring the livelihoods of citizens and strengthening the state's defense capabilities have become extremely important. These sectors will become the locomotive for the recovery of the Ukrainian economy in the future. There is currently no consensus on the list of such industries.Among the existing options, the following should be noted: 1) military-tech (high-tech weapons); metallurgy, mining, and mechanical engineering; agriculture and the food industry; IT sector (Ministry of Economy of Ukraine, 2022); 2) construction and military-industrial complex, among other industries – agro-industrial complex, in particular agriculture, medicine, metallurgy and heavy industry, information technology, education and science, transport and transportation and some others (a survey conducted by the «Rating» group, 2023); 3) agriculture, metallurgy and metalworking, IT sector and startups, among other industries – construction sector, military industry, energy sector and medicine (economic studies, 2022-2024); 4) defense industry, metallurgy and metalworking, power industry, agro-industrial complex, pharmaceutical industry, logistics and infrastructure, natural resources, furniture and woodworking industries, innovations and technologies, industrial manufacturing («Advantage Ukraine», 2022); 5) energy sector, green metallurgy, logistics and transport, IT sector and digitalization, agricultural production (Ministry of Economy of Ukraine, 2024); 6) mechanical engineering, chemical and petrochemical industries, coal, defense and nuclear industries, scientific and scientific-technical activities, agriculture, and healthcare («Concept of a state targeted scientific and technical program for the use of artificial intelligence (AI) technologies in priority sectors of the economy for the period until 2026», 2024).